Aplikasi Pembelajaran Bahasa Mandarin bagi Anak Usia 4-7 Tahun Berbasis Android - Monika Irfanny Wongso; Andreas Handojo; Alexander Setiawan (Jurnal Infra, 2015)
Chinese is a language that's becoming known Nationally and Internationally as well as widely spoken in various walks of life. For this reason, many schools was introduced Chinese language learning from kindergarten. Sometimes kids feel bored using books for learning, because they think that books is not interested and not flexible. Learning Chinese must attractive and flexible to attract children to learn. The use of mobile learning applications installed on the Android device using Eclipse IDE to get data is a way to learning and help the child to be able to learn independently, through features that are provided.Features was provided for learning Chinese is equipped with teaching materials are classified into several categories including learning menu, writing hanzi menu, the exercise menu consisting of quizzes, games and video. To see the development of the child's ability to there is quiz features provided with the assessment contained in the score menu. Based on the results of testing, this learning applications can run well on devices with the Android operating system version 4.1 to 5.0.2, and accessing databases on the admin web it is running well. That’s all to provide children comfort to learning Mandarin. There testing done by giving questionnaires to 10 respondents to determine the level of satisfaction. Based on questionnaires distributed, 50 percent of respondents said they were satisfied with the overall application and another 50 percent said they were very satisfied.